Implementing Screencasts in Educational Settings: Trends, Benefits, and Challenges - Maulana Paramaditya Ananta; Mari'atul Kamila Ramadhan; Anang Prasetyo Aji; Atika Maulidina Hs (Expert Net: Exploration Journal of Technological Education Trends, 2025)
Screencast is a learning medium that records part or all activities on a computer screen accompanied by audio narration providing explanations or instructions aligned with the on-screen actions. This medium is considered effective in supporting the learning process, particularly for delivering procedural content, demonstrations, and reinforcing learners’ understanding. This article aims to examine the implementation of screencast in learning through a Systematic Literature Review (SLR) approach. The review synthesizes findings from previous studies to provide a comprehensive overview of implementation practices, benefits, and challenges of using screencast across various learning contexts. The literature sources were derived from scholarly articles and academic documentation published in reputable and credible journals. The results of this review are expected to contribute both theoretically and practically to the development of technology-enhanced learning strategies and to serve as a reference for educators in optimizing the use of screencast to improve the quality of learning.